Analysis on Port and Maritime Transport System Researches - Lingshan Chen; Xiang Xu; Ping Zhang; Xiaotian Zhang (Journal of Advanced Transportation)
This paper examines the past and current research in the container port and maritime field. Using rigorous bibliometric analysis, the paper identifies the core authors/affiliations, their rankings, and collaboration patterns. The analysis of the paper will enable new researchers to quickly build an understanding of the container port and maritime field by reading core authors’ papers published in specific journals.